Taekwondo coaches knowledge about prevention and management of dental trauma - Vidovic, D.; Goršeta, K.; Bursac, D.; Glavina, D.; Skrinjaric, T. (Collegium Antropologicum, 2014)
The aim of this study was to assess level of knowledge about prevention and dental trauma management among taekwondo coaches in Croatia. The questionnaire submitted to the taekwondo coaches contained 16 items about dental trauma prevention and management. The questionnaires were filled in by 131 taekwondo coaches; 28 females and 103 males. Descriptive statistics was used to describe and analyze the obtained data. The coaches were familiar with dental injuries in high percentage: 41 (31.3%) have observed dental injury and 36 (27.5%) have experienced a dental injury themselves. Eight of them had tooth avulsion, fourteen crown fracture, and eight had tooth luxation. About half of all interviewed coaches 68 (52.7%) were aware of the possibility of replanting avulsed teeth. Twenty six (19.8%) were familiar with the tooth rescue kit. Only 99 out of 131 coaches (75.6%) have used a mouthguard. The obtained results show low knowledge about possibilities for prevention of dental trauma. Insufficient use of mouthguards in this contact sport requires more attention of dentists and coaches education about dental trauma prevention.